Nitrogen Fixation at Paleo‐Mars in an Icy Atmosphere - Danica Adams; Armin Kleinböhl; King‐Fai Li; Franklin P. Mills; Run‐Lie Shia; Robin Wordsworth; Yuk L. Yung (Geophysical Research Letters)
Abstract Recent findings of NO near Gale Crater on Mars have been explained by two pathways: formation of nitric acid (HNO3) in a warm climate or formation of peroxynitric acid (HO2NO2) in a cool climate. Here, we put forth two hitherto unexplored pathways: (a) deposition of nitric/peroxynitric acid onto ice particles in a cold atmosphere, which settle quickly onto Mars' surface and (b) solar energetic particle‐induced production of nitric/peroxynitric acid. The deposition rates are enhanced and NO production is more efficient under the higher atmospheric pressures typical of Mars' ancient atmosphere. Depending on the unknown rate at which nitric/peroxynitric acid is lost from the surface, the new pathways could result in larger NO‐levels than those detected by the Mars Science Laboratory. We predict a 2:1 ratio of nitrite:nitrate would have deposited in cool surface climates with an icy atmosphere, whereas orders of magnitude more nitrate than nitrite is expected from warm surface climates.